Deoxygenation of waste cooking to renewable diesel over walnut shell-derived nanorode activated carbon supported CaO-La2O3 catalyst. (1st November 2017) - Alsultan, G. Abdulkareem; Asikin-Mijan, N.; Lee, H.V.; Albazzaz, Ahmed S.; Taufiq-Yap, Y.H.
Highlights: Nanorode AC supported CaO-La2 O3 render bifunctional acid-base properties. DO of WCO using CaO-La2 O3 /AC focused on decarboxylation/decarbonylation route. Hydrocarbon yield 72% with n -C15 selectivity >80% was achieved. High reusability of CaO-La2 O3 /AC for 5 cycles with yield >63% and n -C15  > 74%. Abstract: Waste cooking oil (WCO) is a potential non-edible feedstock that is sustainable for production of automotive green diesel. The present study focused on synthesis of WCO-derived green diesel through catalytic deoxygenation (DO) process using bimetallic acid-base CaO-La2 O3 /AC nanosized catalyst under zero hydrogen environment. Results indicated that the prepared nano-catalyst rendered high deoxygenation reactivity with 72% yield of straight chain hydrocarbons (C8 -C20 ). The CaO-La2 O3 /AC catalysed reaction pathway favour in decarboxylation/decarbonylation route instead of cracking effect, which consistently formed major n- C15 fractions at approximately >80%. In addition, CaO-La2 O3 /AC showed high catalytic stability and reusability up to 6 cycles with >73% of yield and selectivity to n- C15 of >82%. The catalyst showed an excellent coke inhibitor with less than 2 wt% of coke under TGA analysis.